Electrochemical Corrosion of Oxidized Gamma TitaniumAluminide in Ringer’s Solution: Electrochemical corrosion of oxidized gamma titanium aluminide - Hamidreza Jafarian; Ehsan Saebnoori; Alireza Sabour-Rouhaghdam; Taghi Shahrabi; Mahmoud Nili-Ahmadabadi (Iranian Journal of Pharmaceutical Sciences, 2009)
Ɣ-TiAl intermetallic alloy have a good potential for use as biomaterial, due to its good corrosion resistance. In this paper, two fundamental electrochemical techniques namely electrochemical impedance spectroscopy and potentiodynamic anodic polarization were used to evaluate the corrosion performance of Ɣ-TiAl in Ringer’s solution. Surface modification treatments were employed with the purpose of improving corrosion resistance. The samples were oxidized at 550 °C in air for 1h. The results show that oxidized Ti-47Al-2Cr has much better corrosion resistant in Ringer’s solution. The presence of the oxide layer formed with the surface treatments increased their corrosion resistance. The low values of corrosion rate, and the high values for corrosion potential (Ecorr) and polarization resistance (Rp)obtained experimentally implies that Ɣ-TiAl can be competitively considered as analternative metallic biomaterial.